2012
DOI: 10.1007/s00467-012-2376-5
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of nephrotic syndrome

Abstract: Animal models of proteinuria and nephrotic syndrome are essential tools for studying the mechanisms of action of abnormalities in individual components of the podocyte and glomerular basement membrane. In recent years a variety of in vivo models have been developed to elucidate the function of specific podocyte proteins and their role in the pathogenesis of proteinuria and glomerulosclerosis. In this overview of the animal models currently available we discuss their contribution to our mechanistic understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…The mechanism by which ADR induces podocyte injury has been widely investigated, including both non-immune and immune factors [16,21]. The level of several serum cytokines was assessed in the mice AN model, including TGF-β, IL-6, IL-23, IL-17, IL-10 and IL-4.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which ADR induces podocyte injury has been widely investigated, including both non-immune and immune factors [16,21]. The level of several serum cytokines was assessed in the mice AN model, including TGF-β, IL-6, IL-23, IL-17, IL-10 and IL-4.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has not been proven that platelet alterations play a role in the pathogenesis of the prothrombotic state in NS. Therefore, future research should focus on the pathogenesis of platelet alterations in NS, using an NS animal model, such as puromycin aminonucleoside-treated rats [88]. Furthermore, prospective epidemiologic studies are needed to investigate the relationship between platelet alterations and the incidence of thrombotic complications.…”
Section: Conclusion and Direction Of Future Researchmentioning
confidence: 97%
“…In the kidney, ROS are important causes of acute and subacute renal failure in most cases. Also, in certain animal models of NS, superoxide anions and hydroxyl radicals are the main causes of nephrotoxicity [11]. It has also been reported that renal failure that results from increased ROS and decreased antioxidant enzyme can be prevented by antioxidant therapy [12, 13].…”
Section: Introductionmentioning
confidence: 99%